Metoda raziskave nelinearnih upogibov valjev pri rotacijskem ofsetnem tiskarskem stroju - Augustaitis, Vytautas Kazimieras (Strojniški vestnik, 2006)
The elastic shifts of the plate, blanket and impression cylinders and, initially, the bends of the cylinders that appear during the rotation of the cylinders that are pressed against each other via the thin elastic cloth (blanket) that covers the blanket cylinders (the cylinders are located in suchway that at least one blanket cylinder exists in each pair of cylinders) have a considerable impact on the operation of web offset printing stations. The cylinders are compressed by shifting their bearing assemblies. The method of investigating the mentioned bends of the cylinders and other elastic shiftsas well as the changes of the pressure along the cylinders that are pressed against each other are described. The nonlinear features of the elasticity of the assemblies of the cylinder bearings, the force of gravity and the location of the axes of the rotation of the cylinders with respect to each other are assessed. The problem under discussion is settled as a complex nonlinear static problem, where the required pressures at the edges of the working surfaces of the cylinders that are pressed against each other are provided and the shifts of the assemblies of the cylinder bearings that are required to ensure the said values of the pressures are unknown at the start. On the application of the method to the specified example, it was shown that the bends of the cylinders noticeably impact on the distribution of the pressure along the contact zone of the cylinders in a modern printing press and on the quality of the prints.
Keywords: ofsetni tisk; tiskarski stroji; valji